Synthesis And Mesomorphic Properties Of Symmetric And Non-Symmetric Liquid Crystal Dimers Containing Methylene And Disulphide Spacers - Lee, Huey Charn (2012)
Four series of new symmetric and non-symmetric liquid crystal dimers with multi-functional groups have been synthesised and characterised. Physical and spectroscopic characterisations such as elemental analysis (CHN), infrared spectroscopy (FT-IR) and nuclear magnetic resonance spectroscopy (FT-NMR) have been carried out to elucidate the molecular structures of the dimers. The studies of thermal behaviour and texture observation of the final compounds are performed by means of polarizing optical microscopy (POM) and differential scanning calorimetry (DSC). The first and second series of non-symmetric dimers, α-{4-[(4-substituted-phenylimino)methyl]phenoxy}-ω-[4-(4-pentyloxycarbonylphenyl)phenoxy]alkanes consist of twelve homologues which vary in terms of flexible spacers (pentyl and hexyl) and terminal substituents (H, CH3, C2H5, F, Cl, Br). Investigation on the thermal behaviour shows that the dimers without terminal substituent are not mesogenic while the remaining ten homologues exhibit the nematic phase predominantly. The homologues incorporated with odd-numbered pentyl spacers exhibit the monotropic nematic phase while homologues incorporating the even-numbered hexyl spacers show the enantiotropic nematic phase. Additionally, the homologue with a terminal bromine atom and a hexyl spacer also exhibit a smectic A phase during the cooling cycle. Influence of the terminal substituent size in stabilising the liquid crystalline properties is also studied. Analogous to these dimers, another series of non-symmetric dimers with iodine atom as terminal substituent namely α-{4-[(4-iodophenylimino)methyl]phenoxy}-ω-[4-(4-pentyloxycarbonylphe-nyl)phenoxy]alkanes with spacer ranging from C5H10 to C12H24 have been prepared.